2022
DOI: 10.1038/s43247-022-00523-5
|View full text |Cite
|
Sign up to set email alerts
|

Ecoenzymatic stoichiometry reveals widespread soil phosphorus limitation to microbial metabolism across Chinese forests

Abstract: Forest soils contain a large amount of organic carbon and contribute to terrestrial carbon sequestration. However, we still have a poor understanding of what nutrients limit soil microbial metabolism that drives soil carbon release across the range of boreal to tropical forests. Here we used ecoenzymatic stoichiometry methods to investigate the patterns of microbial nutrient limitations within soil profiles (organic, eluvial and parent material horizons) across 181 forest sites throughout China. Results show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…All these changes can affect soil microbial community composition and activity and drive changes in soil extracellular enzyme production and activity (Chen, Luo, García‐Palacios, et al, 2018; Hedo et al, 2015; Knelman et al, 2015). In turn, extracellular enzymes, secreted primarily by soil microorganisms such as bacteria and fungi (Burns, 1982), can affect soil nutrient cycling processes by catalyzing decomposition of litter and SOM (Chen et al, 2020; Cui et al, 2022; Leinweber et al, 2008; Tan et al, 2020). However, there are major uncertainties about how soil extracellular enzyme activities respond to fire over time.…”
Section: Introductionmentioning
confidence: 99%
“…All these changes can affect soil microbial community composition and activity and drive changes in soil extracellular enzyme production and activity (Chen, Luo, García‐Palacios, et al, 2018; Hedo et al, 2015; Knelman et al, 2015). In turn, extracellular enzymes, secreted primarily by soil microorganisms such as bacteria and fungi (Burns, 1982), can affect soil nutrient cycling processes by catalyzing decomposition of litter and SOM (Chen et al, 2020; Cui et al, 2022; Leinweber et al, 2008; Tan et al, 2020). However, there are major uncertainties about how soil extracellular enzyme activities respond to fire over time.…”
Section: Introductionmentioning
confidence: 99%
“…Our study found that the influence of land-use change was more predominant at the upslope than at the check dam since the erosion processes accelerated nutrient loss. Previous studies have reported a subsequent P limitation of plants after the microbial P limitation (Cui et al 2022;Xue et al 2022), therefore, the P deficiency issue of the revegetated forest on hillslopes should be considered for the local government. It is especially important since the increasing vegetation biomass and water deficiency (Jia et al 2019) would aggravate microbial P limitation with the development of the revegetated forest.…”
Section: Discussionmentioning
confidence: 99%
“…With the empirical balance points derived from the global database (Fig. 2) (Cui et al 2022), the VTC limitation was generally less than zero, and the VTN/P limitation was generally less than zero in cropland (Fig. S2).…”
Section: Microbial Metabolic Limitations Predicted By the Improved V-...mentioning
confidence: 99%
See 2 more Smart Citations